MEWUJUDKAN KELUARGA YANG HARMONIS MELALUI AYAT-AYAT NUSYU>Z DAN SYIQA>Q - Roudhotul Jannah (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
Invention of human is had significance and intention, as invention of a man and a woman. Both of them require each other, like in the family relationship. They have entitlement and obligation to be resposible for their life. If their family relationship has disharmony, as a problem (nusyu>z and syiqa>q). Al-Qur’an give solution to solve it effectively. As we know that the rule of the Qur’an will guide us for happy life in this world and hereafter. Actually Q. Al-Nisa>’ (4): 34 and 35 offer three phase of solution to finish nusyu>z and syiqa>q, like first phase is فَعِظُوهُنَّ, giving good advice or doing persuasive action, etc. The solution of the Qur’anic verses is proportional to make application in human life. So this verses can realize Islam Rahmatan lil ‘Alamîn with happy family, it’s means sakinah mawaddah wa rahmah.